APRESIASI DOSEN PRODI SIYASAH FAKULTAS SYARI’AH DAN HUKUM UIN-SU MEDAN TERHADAP IMPLEMENTASI ETIKA POLITIK ISLAM DALAM PEMILIHAN GUBERNUR SUMATERA UTARA TAHUN 2018 - Syofiaty Lubis; Syafruddin Syam (TAQNIN: Jurnal Syariah dan Hukum, 2021)
The simultaneous regional head elections held in 2018 were one of the largest elections that took place in Indonesia, one of which was in North Sumatra. Its implementation is certainly full of interests for the elected regional head candidates and therefore sometimes they ignore ethics in the process. Practical necessity gives the impression on politics that achieving a goal must justify all means. In Islam, political ethics must be built as a guide for leaders in order to be more sensitive to the needs and benefits of the people. The establishment of good political ethics will give the impression that the authorities uphold the values of justice. In this study, the main focus is to know the appreciation of lecturers in the Siyasah study program at the Faculty of Sharia and Law at UIN North Sumatra Medan for the implementation of Islamic political ethics which took place in the 2018 North Sumatra gubernatorial election.